The population structure of two sympatric hermit-crab species on a subtidal rocky shore of an island in southeastern Brazil - Lima, Daniel J. M. [UNESP]; Cobo, Valter J.; De Aquino, Mariana A. B.; Fransozo, Adilson [UNESP] (Acad Brasileira De Ciencias, 2014)
The main goal of this investigation was to characterize the population structure and shell occupancy of two sympatric hermit-crab species, Pagurus brevidactylus and Paguristes tortugae. The study was undertaken at Couves Island on the southeastern coast of Brazil, from March 2010 through February 2011, on subtidal rocky bottoms. Specimens were collected by SCUBA diving sessions. A total of 195 individuals of P. brevidactylus and 132 of P. tortugae were examined. Both populations showed unimodal size-frequency distributions, which were non-normal for P. brevidactylus and normal for P. tortugae. The median size of P. brevidactylus was significantly smaller than P. tortugae; in both species, males were significantly larger than females. For both, juveniles and ovigerous females were recorded in all size classes and in almost the entire sampling period. No significant departures from the 1: 1 sex ratio were detected, although some size classes were skewed. Overlaps in shell occupation were recorded. Pagurus brevidactylus and P. tortugae showed similar population features; they reached sexual maturity at small sizes, and the nearly year-round presence of young and ovigerous females suggests continuous reproduction. These inter-specific interactions involving resource partitioning suggest a regulatory process that is probably part of the equilibrium strategy of these populations.

Os principais objetivos deste estudo foram caracterizar a estrutura populacional e a ocupação de conchas de duas espécies simpátricas de ermitões, Pagurus brevidactylus e Paguristes tortugae. O estudo foi desenvolvido de março de 2010 a fevereiro de 2011, no sublitoral consolidado da Ilha das Couves, costa sudeste brasileira. Os espécimes foram coletados por meio de sessões de mergulho autônomo. Um total de 195 indivíduos de P. brevidactylus e 132 de P. tortugae foram examinados. Para ambas as populações foram registrados padrões de distribuição unimodal, que foram não normal para P. brevidactylus e normal para P. tortugae. O tamanho mediano para P. brevidactylus foi significativamente menor do que P. tortugae; para as duas espécies, machos foram significativamente maiores do que as fêmeas. Jovens e fêmeas ovígeras foram registrados na maior parte do período amostrado, assim como na maioria das classes de tamanho para ambas as espécies. Não foram verificadas diferenças significativas na proporção sexual 1:1 de ambas as populações, contudo desvios foram registrados em algumas classes de tamanho. Foram registradas sobreposições na utilização de conchas. Para P. brevidactylus e P. tortugae foram registradas características populacionais semelhantes; atingem a maturidade sexual em classes de tamanho iniciais, e a presença de jovens e fêmeas ovígeras em quase todo período de estudo sugere que tenham reprodução contínua. Essas interações interespecíficas envolvendo a partilha de recursos indica um processo de regulação, que provavelmente, está incluído na estratégia de equilíbrio dessas populações.
Keywords: Continuous reproduction; Rocky bottoms; Shell partitioning; Sympatric species; Reprodução contínua; Sublitoral consolidado; Partilha de conchas; Espécies simpátricas